PfATP4 inhibitors in the Medicines for Malaria Venture Malaria Box and Pathogen Box block the schizont-to-ring transition by inhibiting egress rather than invasion - Barnes, Claudia B. G.; Dans, Madeline G.; Jonsdottir, Thorey K.; Crabb, Brendan S.; Gilson, Paul R. (Frontiers in Cellular and Infection Microbiology, 2022)
The cation efflux pump Plasmodium falciparum ATPase 4 (PfATP4) maintains Na+ homeostasis in malaria parasites and has been implicated in the mechanism of action of many structurally diverse antimalarial agents, including >7% of the antimalarial compounds in the Medicines for Malaria Venture’s ‘Malaria Box’ and ‘Pathogen Box’. Recent screens of the ‘Malaria Box’ and ‘Pathogen Box’ revealed that many PfATP4 inhibitors prevent parasites from exiting their host red blood cell (egress) or entering new host cells (invasion), suggesting that these compounds may have additional molecular targets involved in egress or invasion. Here, we demonstrate that five PfATP4 inhibitors reduce egress but not invasion. These compounds appear to inhibit egress by blocking the activation of protein kinase G, an enzyme that, once stimulated, rapidly activates parasite egress. We establish a direct link between egress and PfATP4 function by showing that the inhibition of egress is attenuated in a Na+-depleted environment and in parasites with a mutation in pfatp4. Finally, we show that PfATP4 inhibitors induce host cell lysis when administered prior to the completion of parasite replication. Since host cell lysis mimics egress but is not followed by invasion, this phenomenon likely explains why several PfATP4 inhibitors were previously classified as invasion inhibitors. Collectively, our results confirm that PfATP4-mediated Na+ efflux is critical to the regulation of parasite egress.